Forgetting To Remember : Remembering To Forget: a space for reconciliation and transformation in post-apartheid South Africa - Gevers, Katja Barros (School of Architecture, Planning and Geomatics, 2014)
This dissertation discusses the origin, development and implementation of the design project - a reconciliation memorial in the Schotschekloof quarry in Cape Town. The project aims to illuminate the opportunity for architecture to engender reconciliation, and therefore contribute, however subtly, towards the transformation of a society. It is applied to the South African post-Apartheid context through the lens of the Truth and Reconciliation Commission, but deals with universal themes of memory, loss and forgiveness. The project critically explores reconciliation resulting from the interplay of memory and forgetting within the spatial confines of the memorial. It explores the functional aspects of both processes expanding on the traditional definition of commemorative space in art and architecture.